Pre-Weaning Growth Hormone Treatment Reverses Hypertension and Endothelial Dysfunction in Adult Male Offspring of Mothers Undernourished during Pregnancy - Gray, Clint (Public Library of Science, 2013)
Maternal undernutrition results in elevated blood pressure (BP) and endothelial dysfunction in adult offspring. However, few studies have investigated interventions during early life to ameliorate the programming of hypertension and vascular disorders. We have utilised a model of maternal undernutrition to examine the effects of pre-weaning growth hormone (GH) treatment on BP and vascular function in adulthood. Female Sprague-Dawley rats were fed either a standard control diet (CON) or 50% of CON intake throughout pregnancy (UN). From neonatal day 3 until weaning (day 21), CON and UN pups received either saline (CON-S, UN-S) or GH (2.5 ug/g/day)(CON-GH, UN-GH). All dams were fed ad libitum throughout lactation. Male offspring were fed a standard diet until the end of the study. Systolic blood pressure (SBP) was measured at day 150 by tail cuff plethysmography. At day 160, intact mesenteric vessels mounted on a pressure myograph. Responses to pressure, agonist-induced constriction and endothelium-dependent vasodilators were investigated to determine vascular function. SBP was increased in UN-S groups and normalised in UN-GH groups (CON-S 121±2 mmHg, CON-GH 115±3, UN-S 146±3, UN-GH 127±2). Pressure mediated dilation was reduced in UN-S offspring and normalised in UN-GH groups. Vessels from UN-S offspring demonstrated a reduced constrictor response to phenylephrine and reduced vasodilator response to acetylcholine (ACh). Furthermore, UN-S offspring vessels displayed a reduced vasodilator response in the presence of L-NG-Nitroarginine Methyl Ester (L-NAME), carbenoxolone (CBX), L-NAME and CBX, Tram-34 and Apamin. UN-GH vessels showed little difference in responses when compared to CON and significantly increased vasodilator responses when compared to UN-S offspring. Pre-weaning GH treatment reverses the negative effects of maternal UN on SBP and vasomotor function in adult offspring. These data suggest that developmental cardiovascular programming is potentially reversible by early life GH treatment and that GH can reverse the vascular adaptations resulting from maternal undernutrition.